2016
DOI: 10.1080/01635581.2016.1224370
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial to Increase Navy Bean or Rice Bran Consumption in Colorectal Cancer Survivors

Abstract: Consumption of navy beans (NB) and rice bran (RB) have been shown to inhibit colon carcinogenesis. Given the overall poor diet quality in colorectal cancer (CRC) survivors and low reported intake of whole grains and legumes, practical strategies to increase consumption merit attention. This study determined feasibility of increasing NB or RB intake in CRC survivors to increase dietary fiber and examined serum inflammatory biomarkers and telomere lengths. Twenty-nine participants completed a randomized-controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 55 publications
0
64
0
1
Order By: Relevance
“…Therefore, reduction of Firmicutes may provide some protection against CRC. Both NBP and SRB increased total fiber in the participants’ diets ; and while NBP increased gut bacterial richness, it did not change the F:B ratio. Furthermore, NBP had two to five differentiating bacterial taxa at 14 and 28 days compared to 20+ for SRB (Supporting Information Table 2).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Therefore, reduction of Firmicutes may provide some protection against CRC. Both NBP and SRB increased total fiber in the participants’ diets ; and while NBP increased gut bacterial richness, it did not change the F:B ratio. Furthermore, NBP had two to five differentiating bacterial taxa at 14 and 28 days compared to 20+ for SRB (Supporting Information Table 2).…”
Section: Discussionmentioning
confidence: 81%
“…All participants provided written informed consent prior to enrollment. Participant recruitment, exclusion criteria, study design, and sample collection is described in detail in Borresen et al [32].…”
Section: Participants Study Design and Sample Collectionmentioning
confidence: 99%
“…85 A heat-stabilized rice bran diet offers the benets of bacterial richness and diversity in the gut, helps with microbial metabolism, modulates stool metabolite proles, and contributes to chemoprevention in colorectal cancer survivors. [86][87][88] The function of rice bran in altering gut microbiota might contribute to the relief of adverse gastrointestinal effects in cancer patients during chemotherapy. A study that enrolled patients with cervical cancer indicated that the oral intake of hydrolyzed rice bran effectively attenuated the diarrheal side effects of chemotherapy.…”
Section: Clinical Trialsmentioning
confidence: 99%
“…Polished white rice is the major product with rice milling yields of 65-70% and the by-products comprised of 20% rice husk and 8-12% rice bran [8]. Rice bran has a broad spectrum of health benefits [9][10][11][12], partially due to a diverse array of bioactive metabolites [13,14]. Rice bran bioactive components include, but are not limited to γ-oryzanol [15], tocopherols, tocotrienols [16], carotenoids [17], γ-aminobutyric acid [18], octacosanol [19], squalene [20], unsaturated fatty acids [21], phytosterols and phenolic compounds [22].…”
Section: Introductionmentioning
confidence: 99%